Strategi Perlokusi Iklan Komersial Berbahasa Indonesia di Facebook dan Tiktok: Implikasi Terhadap Perilaku Konsumen - Neni Surya Nirmala; Zul Haeri (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study aims to describe the forms of perlocutionary effects and language strategies in Indonesian-language commercial advertisements on Facebook and TikTok. This study employs a qualitative descriptive method with a pragmatic approach. Data were collected through observation and note-taking on commercial advertisements across the categories of beauty products, food and beverages, financial services, fashion, and digital entertainment during the period of January–March 2025. The results indicate that in beauty and nutrition product advertisements, perlocutionary effects manifest as cognitive beliefs; in financial services advertisements, as perceptions of affordability; in fashion advertisements, as self-identification; and in digital entertainment advertisements, as emotional engagement. The primary strategies identified include the use of numerical data claims to build credibility, life-scenario narratives for self-identification, and directive operational instructions to encourage immediate action. Interactive characteristics of social media, such as the comment response format on TikTok, were found to amplify perlocutionary power by creating the illusion of personal communication—a condition where the audience feels directly and individually addressed by the advertiser, even though the message is simultaneously directed at millions of users. Digital context and human presenter engagement emerged as the primary determinants of message effectiveness. This research confirms that advertising language on social media functions as a strategic instrument capable of directing the audience’s perceptions and economic behavior through psychological and linguistic manipulation integrated with platform features